A Case of Neuropsychiatric Systemic Lupus Erythematosus With Hair Loss as the First Diagnostic Symptom - He, Xun; Duan, Xi-Ling; Liu, Jing-Song (Frontiers in Psychiatry, 2022)
Neuropsychiatric systemic lupus erythematosus is a serious complication of systemic lupus erythematosus. A 33-year-old female patient had repeated hair loss for more than 3 years. A dermatologic examination showed several pieces of irregularly shaped hair loss patterns in the center of the patient's scalp. The systemic treatment included oral hydroxychloroquine, aspirin enteric-coated tablets and prednisone, and intrathecal injection of dexamethasone and methotrexate. The local treatment included intralesional injection of triamcinolone acetonide and lidocaine in the lesion area, 0.1% tacrolimus ointment for external use. After 2-month treatment, hair regrew in a non-scarring patchy alopecia region with no further hair loss.